Kontribusi Islam Terhadap Akuntansi - Sabrina, Ivo (Al-Iqtishad: Journal of Islamic Economics, 2012)
This study will focus on the comparison between the accounting and another definition to find the harmony and unity of meaning in it. This study uses the approach of the historical development and significance of accounting in Islam. The meaning of accounting from Quran and Hadith perspective is general and covers the whole of human activity in the lives interact and transaction each other, either in religous and related fields or in muamalah areas and socio-economics transactions in general.DOI: 10.15408/aiq.v4i2.2102